Altered heme metabolism and hemoglobin concentration due to empirical antibiotics-induced gut dysbiosis in preterm infants - Seung Hyun Kim; Min‑Jin Kwak; Jae Kyoon Hwang; Jihyun Keum; Hee Yeon Jin; Chan-Yeong Lee; Rahul Sadashiv Tanpure; Yong Joo Kim; Jeong-Kyu Hoh; Jae Yong Park; Woojin Chung; Byong-Hun Jeon; et al. (Computational and Structural Biotechnology Journal)
Background: High-risk infants are usually treated with empirical antibiotics after birth, regardless of the evidence of infection; however, their gut microbiome and metabolome have seldom been studied. This study investigated the influence of antibiotic exposure on the gut microbiome and associated metabolic pathways in term and preterm infants. Methods: Thirty-six infants within 10 days of birth who were admitted to a neonatal intensive care unit/newborn nursery unit were divided into four groups based on maturity (gestational age) and use of empirical antibiotics. Genomic DNA was extracted from the fecal samples and underwent high-throughput 16S rRNA amplicon sequencing using the Illumina platforms. Taxonomic classification, diversity analysis, and metagenomic function prediction were performed. Results: Preterm infants with empirical antibiotics showed a significantly decreased population of Firmicutes (p = 0.003) and an increased population of Proteobacteria (p < 0.001) compared to other groups. At the genus level, the populations of Raoultella (p = 0.065) and Escherichia (p = 0.052) showed an increased trend. The change in microbial composition was correlated with increased heme biosynthesis and decreased hemoglobin levels. Conclusion: Collectively, our finding suggested that empirical antibiotic exposure in preterm infants alters the gut microbiome, potentially leading to adverse health outcomes. This dysbiosis may affect heme metabolism, increasing the risk of anemia in these vulnerable infants. Therefore, antibiotic use should be carefully tailored to minimize potential harm.